Imigranci na norweskim rynku pracy - Joanna Napierała (University of Warsaw, Centre of Migration Research (CMR), 2008)
– This study analyses the Norwegian labour market, focusing on changes that have taken place, and on problems that have surfaced in the past decade. The study helps identify the main determinants of the demand for foreign labour in Norway, as well as of factors that are likely to shape the scale and the composition of the demand for foreign labour in Norway in the near future. The study includes a short description of the history of migration to Norway, and a description of the main migrant groups in the country. It also presents results of research carried out on the position of migrant workers in the Norwegian labour market. In view of the substantial increase in the past three years in the inflow of Polish migrants to Norway, the last part of the study offers a detailed analysis of this group of migrants.
Keywords: 330; Arbeitsmarkt; Migranten; Arbeitsmigranten; Polen (Personen); Norwegen